Analysis of Fix Price Travel Tran sport Based on Vehicle Operational Costs - Maulvi Dwi Agustyo; Murniati Murniati; Ina Elvina (PT Mattawang Mediatama Solution, 2024)
Transportation become an important role in a variety of human needs that are quite diverse, such as economic needs, education, health, and others. This study calculated the Operating Costs of Travel Vehicles on the Palangka Raya - Tamiang Layang City route, using the 2002 Directorate General of Land Transportation method. The method is in the form of an interview survey, analyzing Vehicle Operating Cost data from travel transport service providers with the Palangka Raya- Tamiang Layang City route, namely CV. Putra Borneo Travel, CV. New Star Travel, and CV. Trans Kalimantan Travel. This study aims to determine the Operating Cost of Travel Vehicles on the Palangka Raya - Tamiang Layang route to find out how much the basic rate set is financially feasible for service providers. The findings from the value analysis of the Operating Cost of Travel Vehicles on the Palangka Raya- Tamiang Layang route reveal that CV. Putra Borneo Travel incurred IDR 4,934.61, CV. Trans Kalimantan Travel incurred IDR 4,253.21, and CV. Bintang Baru Travel incurred IDR 4,733.95. The basic passenger rate set is financially feasible for service providers by, CV. Putra Borneo Travel at IDR 295,056/pnp, CV. Trans Kalimantan Travel at IDR 254,324/ pnp, CV. Bintang Baru Travel at IDR 283,071/ pnp. The rates issued by the three travel transportation service providers are IDR 230,000/ pnp.